Into performance : Japanese women artists in New York - Yoshimoto, Midori (Rutgers University Press, 2005)
The 1960s was a time of incredible freedom and exploration in the art world, particularly in New York City, which witnessed the explosion of New Music, Happenings, Fluxus, New Dance, pop art, and minimalist art. Also notable during this period, although often overlooked, is the inordinate amount of revolutionary art that was created by women. Into Performance fills a critical gap in both American and Japanese art history as it brings to light the historical significance of five women artists-Yoko Ono, Yayoi Kusama, Takako Saito, Mieko Shiomi, and Shigeko Kub.